The impact of state policy on the development of organic agriculture in Azerbaijan - Mehriban Aliyeva; Gulnara Tanriverdiyeva; Dilbar Faradjova; Esmira Ahmadova; Oksana Baranovska (Наукові горизонти, 2024)
The purpose of this study was to analyse the impact of government policy on the development of organic agriculture in Azerbaijan and to assess the effectiveness of support programmes for organic farmers. The methodology included an analysis of legislative documents, government support programmes for farmers, and reports of state and international organizations. The study found that organic agriculture in Azerbaijan is actively supported through legislative initiatives, such as the Law of the Republic of Azerbaijan No. 650-IIIQ “On Ecologically Clean Agriculture”, adopted in 2008, and government support programmes. The law prohibits the use of genetically modified organisms and chemicals, and sets standards for the certification of organic products. As of 2020, the area of certified organic land was 40,779 hectares, indicating significant potential for the sector. The Azerbaijan 2020: Looking to the Future programme provides financial support to farmers by providing subsidies for fertilizers, seeds and other inputs that contribute to the development of organic production. In 2021-2022, AZN 61.8 million was paid to support agriculture. The study also identified significant challenges, including high certification costs, limited access to modern technologies and low demand for organic products in the domestic market, where only 15% of organic goods are sold. According to forecasts, with increased government support, the area of organic land could reach 500,000 hectares by 2030, which would help increase exports and improve the competitiveness of organic products in international markets. Further development also requires improving infrastructure and creating new sales channels for organic products